Spillover HIV prevention effects of a cash transfer trial in East Zimbabwe: evidence from a cluster-randomised trial and general-population survey - Robin Schaefer; Ranjeeta Thomas; Laura Robertson; Jeffrey W. Eaton; Phyllis Mushati; Constance Nyamukapa; Katharina Hauck; Simon Gregson (BMC, 2020)
Abstract Background Benefits of cash transfers (CTs) for HIV prevention have been demonstrated largely in purposively designed trials, commonly focusing on young women. It is less clear if CT interventions not designed for HIV prevention can have HIV-specific effects, including adverse effects. The cluster-randomised Manicaland Cash Transfer Trial (2010-11) evaluated effects of CTs on children's (2-17 years) development in eastern Zimbabwe. We evaluated whether this CT intervention with no HIV-specific objectives had unintended HIV prevention spillover effects (externalities). Methods Data on 2909 individuals (15-54 years) living in trial households were taken from a general-population survey, conducted simultaneously in the same communities as the Manicaland Trial. Average treatment effects (ATEs) of CTs on sexual behaviour (any recent sex, condom use, multiple partners) and secondary outcomes (mental distress, school enrolment, and alcohol/cigarette/drug consumption) were estimated using mixed-effects logistic regressions (random effects for study site and intervention cluster), by sex and age group (15-29; 30-54 years). Outcomes were also evaluated with a larger synthetic comparison group created through propensity score matching. Results CTs did not affect sexual debut but reduced having any recent sex (past 30 days) among young males (ATE: − 11.7 percentage points [PP] [95% confidence interval: -26.0PP, 2.61PP]) and females (− 5.68PP [− 15.7PP, 4.34PP]), with similar but less uncertain estimates when compared against the synthetic comparison group (males: -9.68PP [− 13.1PP, − 6.30PP]; females: -8.77PP [− 16.3PP, − 1.23PP]). There were no effects among older individuals. Young (but not older) males receiving CTs reported increased multiple partnerships (8.49PP [− 5.40PP, 22.4PP]; synthetic comparison: 10.3PP (1.27PP, 19.2PP). No impact on alcohol, cigarette, or drug consumption was found. There are indications that CTs reduced psychological distress among young people, although impacts were small. CTs increased school enrolment in males (11.5PP [3.05PP, 19.9PP]). Analyses with the synthetic comparison group (but not the original control group) further indicated increased school enrolment among females (5.50PP [1.62PP, 9.37PP]) and condom use among younger and older women receiving CTs (9.38PP [5.90PP, 12.9PP]; 5.95PP [1.46PP, 10.4PP]). Conclusions Non-HIV-prevention CT interventions can have HIV prevention outcomes, including reduced sexual activity among young people and increased multiple partnerships among young men. No effects on sexual debut or alcohol, cigarette, or drug consumption were observed. A broad approach is necessary to evaluate CT interventions to capture unintended outcomes, particularly in economic evaluations. Trial registration ClinicalTrials.gov , NCT00966849 . Registered August 27, 2009.